Redistributive Effect and the Progressivity of Taxes and Benefits: Evidence for the UK, 1977-2018 - Nicolas Herault; Stephen P. Jenkins (Institute of Labor Economics (IZA), 2021)
We apply the Kakwani approach to decomposing redistributive effect into average rate, progressivity, and reranking components using yearly UK data covering 1977-2018. We examine cash and in-kind benefits, and direct and indirect taxes. In addition, we highlight an empirical implementation issue - the definition of the reference ('pre-fisc') distribution. Drawing on an innovative counterfactual approach, our empirical analysis shows that trends in the redistributive effect of cash benefits are largely associated with cyclical changes in average benefit rates. In contrast, trends in the redistributive effects of direct and indirect taxes are mostly associated with changes in progressivity. For in-kind benefits, changes in the average benefit rate and progressivity each played the major roles at different times.
Keywords: D31; H24; H50; I38; 330; reranking; Kakwani decomposition; inequality; redistributive effect; progressivity; benefits; taxes